Editorial: Memory - Humanities and Social Sciences Contexts - Bożena Sieradzka-Baziur (Jesuit University Ignatianum in Krakow, 2017)
Memory  is one of the essential concepts of science and it is presents in scientific works of psychology, pedagogy, sociology, linguistics, history, cultural studies, and also i.e. neurobiology or computer science...